Motor strategy for rapid gait initiation under conditions of limited center of pressure control - Yoshida, Takayuki (J Phys Ther Sci, 2019)
[Purpose] The general motor strategy for gait initiation is achieved by the difference between the center of gravity and center of pressure; it be as bigger under speed optimization. This study aimed to investigate the motor pattern in rapid gait initiation under conditions of limited backward displacement of center of pressure. [Participants and Methods] The participants were 30 healthy young males (mean age, 19.7 ± 1.0 years). They performed a gait initiation task at three center of pressure start positions (anterior, middle, and posterior) and two speed conditions (normal and rapid). The gait initiation motion was measured using a video camera and motor pattern in the images was classified. The center of pressure position was continuously monitored using a pressure distribution measurement system. [Results] Forward tilt pattern was the most common under no limited center of pressure control and normal speed. The backward tilt pattern was the most preferred in the posterior position under limited center of pressure control and rapid speed. Displacement of the center of pressure showed a significant decline when the center of pressure start position was displaced backward. [Conclusion] The backward tilt pattern is the most effective motor strategy to increase the forward speed of the center of gravity.